Investigation of TiAlC by Atomic Layer Deposition as N Type Work Function Metal for FinFET. (1st January 2015) - Xiang, Jinjuan; Li, Tingting; Zhang, Yanbo; Wang, Xiaolei; Gao, Jianfeng; Cui, Hushan; Yin, Huaxiang; Li, Junfeng; Wang, Wenwu; Ding, Yuqiang; Xu, Chongying; Zhao, Chao
Abstract : TiAlC film grown by thermal atomic layer deposition (ALD) technique was investigated as N type work function metal for high-k dielectric/metal gate (HKMG) last FinFET integration, due to the excellent conformality and precise thickness control of ALD. The TiAlC film was deposited using titanium tetrachloride and trimethylaluminum. The physical characteristics of the TiAlC film such as chemical composition, growth rate, resistivity, surface roughness, and crystal morphology were investigated by X-ray photoemission spectroscopy, X-ray reflectivity, four point probe method, atomic force microscopy and X-ray diffraction, respectively. The major content of the film is found to be TiAlC. The growth rate increases with the growth temperature while the resistivity and the surface roughness decrease with the growth temperature. The as deposited film shows no additional obvious crystalline peaks compared with the reference bare Si, which indicates the film is amorphous. The electrical characteristics of the TiAlC film were investigated by using metal-oxide-semiconductor capacitors for capacitance-voltage measurement. The effective work function of the TiAlC film can be tuned from 4.49 eV to 4.79 eV using growth temperature, TMA dose and film thickness. It is found that the ALD TiAlC film is a promising gate metal candidate for HKMG last FinFET integration.